Professional identity influence mechanism of students majoring in mining with a view to sustainable development - Shijie Gao; Shijie Gao; Xigui Zheng; Ying Wang (Frontiers in Psychology)
IntroductionThis study explores the mediating role of behavioral engagement in the relationship between professional identity (PI) and sustainable competence among mining engineering students.MethodsDrawing on a structural equation model (SEM), the research investigates how PI influences students’ sense of fulfillment (SF) through personal behavior (PB). Data were collected from 1,007 mining students across China.ResultsThe findings reveal that PI significantly enhances SF both directly (β = 0.562, p < 0.001) and indirectly through PB (β = 0.425, p < 0.001). While environmental, peer, and curriculum factors were hypothesized to influence PI, their direct effects were not statistically significant.DiscussionThe study underscores the critical role of PI in fostering sustainable competence and highlights PB as a key mediator in this process. These results offer valuable insights for educational institutions aiming to cultivate professional identity and sustainable development among students in high-risk industries like mining. Practical recommendations include strengthening PI education, fostering positive PB, and optimizing external cultural and curricular environments to enhance students’ academic and professional outcomes.